Analysis of profitability of banks: comparative study of domestic and foreign banks in Malaysia - Shee, Li Hua (2018)
The banking system plays a very important in the growth of economy. The objective of this research study is to analyse and compare the financial performance of domestic commercial banks and foreign commercial banks which are operating in Malaysia during the period of 2007-2016. It is also aims to examine the relationship between bank’s profitability with bank size and credit risk. This study is useful for depositors, bank managers, shareholders, investors, regulators and researchers in order to provide a true picture of domestic commercial banks and foreign commercial banks. The research questions of this study are: (1) Is there any difference between both type of banks in terms of profitability? (2) Is there any relationship between bank size and the profitability of banks in Malaysia? (3) Is there any relationship between credit risk and the profitability of banks in Malaysia?. A sample of domestic commercial banks and foreign commercial banks are used in the research. The list of domestic commercial banks and foreign commercial banks is obtained from Bank Negara Malaysia’s (BNM) website. Data had been generated from DataStream and banks’ annual reports. The sources of banks’ annual reports are from the websites of the banks and also Bloomberg. The significant of data has been determined using independent sample t-test, one-way ANOVA analysis and multiple regression. Study has concluded that domestic commercial banks are less profitable in term of Return on Average Assets (ROAA), Return on Average Equity (ROAE) and Net Interest Margin (NIM) as compared to foreign commercial banks. Whereas, for Net Interest Income/ Recurring Revenue, domestic commercial banks are significantly profitable compared to foreign commercial banks. ROAA and ROAE has a significant negative relationship with bank size and credit risk. NIM has significant positive relationship with credit risk, but no relationship with bank size. Whereas, NIIRR has significant positive relationship with bank size, but no relationship with credit risk. A few ideas are recommended for future research i.e. increase the data period, increase the independent variables and explore other possible areas like foreign Islamic banking vs domestic Islamic banking.